Dispersion measurement of optical fibers by phase retrieval from spectral interferometry. (7th April 2017) - Qi, W; Huang, X; Ho, D; Yoo, S; Yong, K T; Luan, F
Abstract: We report a simple and fast dispersion measurement method to determine optical fiber dispersion directly from interference phase. Compared to the prior interferometer based dispersion measurements, our method can effectively and accurately extract phase from the interference spectrum. The method allows us to obtain dispersion even when the spectrum is distorted by wavelength dependent power variation. The measurement is experimentally demonstrated, employing a Mach–Zenhder interferometer using a white light source, and the results are theoretically verified. The presented method shows excellent accuracy in a conventional single mode fiber regardless of location of a zero dispersion wavelength. We also confirm that the technique is effective to measure dispersion of a micro-structured optical fiber when an interference spectrum is largely distorted by oscillating baseline spectra.